EYE TRACKING IN POSTERIOR CORTICAL ATROPHY: A NEW INSIGHT INTO THE VISUAL SYNDROME. (29th November 2012) - Shakespeare, T; Crutch, S
Abstract : Visual disorientation is a common and disabling symptom in Posterior Cortical Atrophy (PCA). However few studies of point localisation skills have been conducted, and it remains unclear to what extent such deficits in PCA are attributable to visuospatial deficits or impoverished eye movement control. Three tasks were administered: (i) fixation stability task (ii) pro-saccade task for 8 close and 8 distant targets; and (iii) motion pro-saccade task (localisation of static targets and targets containing motion information). Participants in experiments (i) and (ii) were seven patients with a clinical diagnosis of PCA and six healthy controls, four PCA patients and three controls undertook experiment (iii). Eye movements were measured using the Eyelink II pupil tracking system. (i) Patients demonstrated shorter fixation durations and greater fixation location error than controls. (ii) Patients' saccade latency and distance of first saccade was greater than that of controls for distant but not close targets (see figure 1). (iii) Patients showed a trend towards lower latency for the jittering stimulus. The jitter stimulus in controls, and the looming stimulus in patients showed a trend towards lower directional accuracy. The results demonstrate poor fixation stability and eye control in PCA. The pro-saccade results are consistent with the suggestion of reduced effective field of vision in PCA. Eye tracking provides insight into mechanisms behind key deficits in PCA and permits evaluation of cues to improve localisation.